Problematika Maharah Qira’ah Pada Pembelajaran Al-Quran di Madrasah Diniyah Manba’ul Ulum Desa Kedungbanteng Sukorejo Ponorogo - Kusuma, Eka; Putra, Wahyu Hanafi; Setyowati, Nanik (Institut Agama Islam Sunan Giri Ponorogo, 2024)
The problem of learning in madrasah diniyah is a problem that hinders religious teaching and learning activities. Maharotul kalam is a skill that is applied with speech and also has a relationship with language. From the title, I took 2 problem formulations, namely how the learning process of maharatul kalam and what are the factors that hinder learning. From the formulation of the problem, there are several objectives, namely to know, explore, and learn how the learning process is and what are the factors that hinder learning at the madrasah Diniyah Manba'ul Ulum. This research is using a qualitative method. Data collection techniques use interviews, observations and documents. The data analysis technique uses data reduction analysis, data presentation, and conclusion drawn. This study uses primary data and secondary data. The results of the study show that Maharah Kalam Problems in Learning the Quran need to improve learning so that students and women can absorb the material and read the Quran smoothly and well according to what they want, besides that there are 2 factors, namely non-linguistic problems and linguistic problems. This is evident from the results of interviews and direct observation on objects.